Peningkatan Prestasi Belajar Siswa Kejuruan Melalui Model Pembelajaran Think, Talk, and Write (TTW) - Sulimah, Sulimah; Sulistya, Darmanta; Fitri, Sulidar (FKIP Universitas Lampung, 2018)
This study was aimed to improve the learning achievement of reinforced concrete construction that had not reached the Pre-Determined Minimum Criteria of Standard Mastery (KKM) through the implementation of Think Talk and Write (TTW) learning model. This research involved 31 students of SMK in Wonosari Sub-District, Gunung Kidul Regency, Yogyakarta. The research design used was Classroom Action Research (PTK) one cycle consisting of: (1) planning, (2) implementation, (3) observation, and (4) reflection. Data collection techniques used were observation techniques, questionnaires, testing, and documentation analyzed by qualitative and quantitative descriptive techniques. The instruments used were observation sheets, questionnaires, interview guides, and test instruments. The results showed that the TTW learning model significantly improved the achievement of student learning outcomes. The results were shown from the results of the percentage of students’ learning mastery in the first cycle with the number of 18 students showed the percentage of 58.06% and the second cycle with the number of 27 students showed a percentage of 87.1%, so there was a 25.8% increase. In addition, the TTW learning model was able to improve student’s learning activities from first cycle to second cycle with the average gain value of 0.3625 which indicates that the inhancement of student’s learning activities was in the medium category. The overall increase in student activity and learning outcomes was supported by the students’ positive responses to learning that applied the TTW learning model. Keywords: Learning, Think Talk and Write (TTW), Learning Achievement.DOI: http://dx.doi.org/10.23960/jpp.v8.i1.201805